2018
DOI: 10.1111/jcal.12284
|View full text |Cite
|
Sign up to set email alerts
|

The effects of biofeedback‐based stimulated recall on self‐regulated online learning: A gender and cognitive taxonomy perspective

Abstract: Previous studies posited the effectiveness of stimulated recall. However, few studies explored how SR is implemented in a relatively static context, for example, online selfdirected learning, or took human factors, for example, cognitive style and gender, into consideration in such a context. To fill this gap, the current study, aims to introduce biofeedback as a stimulus for learners to engage in retrospection regarding their learning behavior. A quasi-experimental design study was carried out over a 12-week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The interaction between an individual and an environment is considered as an extremely critical factor in understanding individuals and determining their behaviors [21]. The model of person-environment interaction proposed by Moos [22] focused on the bi-directional relationship between people and environments that is correlated to a range of various states in the psychological and physical domains, such as cognitive [23] and motivation [24]. In an online learning environment, based on person-environment interaction theory, Neufeld et al [21] proposed that academic constructs (e.g., learning persistence and engagement) reflected the interaction between a student and his or her educational environment.…”
Section: Person-environment Interaction Modelmentioning
confidence: 99%
“…The interaction between an individual and an environment is considered as an extremely critical factor in understanding individuals and determining their behaviors [21]. The model of person-environment interaction proposed by Moos [22] focused on the bi-directional relationship between people and environments that is correlated to a range of various states in the psychological and physical domains, such as cognitive [23] and motivation [24]. In an online learning environment, based on person-environment interaction theory, Neufeld et al [21] proposed that academic constructs (e.g., learning persistence and engagement) reflected the interaction between a student and his or her educational environment.…”
Section: Person-environment Interaction Modelmentioning
confidence: 99%
“…Moreover, eye-tracking technology has been used for the study of reading comprehension and memory-related tasks among students. Zhai et al [16] found that SRL techniques improved reading comprehension. They likewise found differences relating to scan-paths between men and women.…”
Section: Areas Of Application Of Eye-tracking Technologymentioning
confidence: 99%
“…For example, the eye-tracking technique could capture learners' eye fixation to track the attended area, but the reasons for the foci may be attributed to different affections such as interest, anxiety, or even distraction. An additional source of data such as EEG could help to make a more accurate assessment [52].…”
Section: E Categories Of the Application Dimensionmentioning
confidence: 99%